Temporal dynamics of soil erosion in coffee (Coffea arabica), Llano Brenes, Costa Rica - Palominos-Rizzo, Teresa (2022)
Introduction. Water erosion is a natural phenomenon accelerated by human activity, which facilitates soil degradation and sediment transport to other areas. Objective. To quantify the surface runoff and erosion rate at the plot scale, under natural precipitation events in an Entisol soil cultivated with shaded coffee (Coffea arabica) and to determine the temporal dynamics and the influence of the main factors associated with this process. Materials and methods. The study was developed in Llano Brenes, Alajuela, Costa Rica. Nine runoff plots were installed, the data was collected between May 2018 and November 2019, each plot had a runoff meter and a container for collecting sediment samples. Three-time domain reflectometry sensors were installed for surface soil moisture content measurements. Data analysis was carried out on a monthly-annual, inter-event and intra-event scale. At the intra-event scale, the Diskin & Nazimov infiltration model was applied. Results. In the years 2018 and 2019, the following annual results were obtained, respectively: a) total runoff sheet of 90.99 and 102.66 mm, b) sediment concentration of 2.14 and 1.88 g L-1, and c) soil loss of 1612 and 1692 g m-2. The highest soil loss values were obtained in October of each year. The intra-event analysis explained the runoff generation based on the precipitation sheet and the initial moisture content in the event. Conclusion. The mean annual erosion rate and runoff were 1652 g m-2 and 96.8 mm. The precipitation sheet, intensities, and initial surface soil moisture content played an important role in runoff generation and soil loss.